Pengaruh Capital Adequacy Ratio (Car), Financing To Deposit Ratio (Fdr), Non Performing Financing Npf), Net Operating Margin (Nom) Terhadap Profitabilitas Dengan Biaya Operasional Per Pendapatan Operasional (Bopo) - Nining Ailiyah (LAN TABUR : Jurnal Ekonomi Syariah, 2020)
The purpose of this study was to determine and analyze the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing NPF, Net Operating Margin (NOM) on Profitability with Operating Costs per Operating Income (BOPO).The population used in this study were Javanese Islamic banking companies registered with the Financial Services Authority. The data is a time-series cross-section data from 2013-2016. The data collection method used is secondary data available on the official. To analyze it, researchers used a path analysis model or path analysis.The formulations in this study are: 1) How is the Capital Adequacy Ratio, Non-Performing Financing, Financing Debt Ratio, Net Operating Margin, Operational Costs per Operating Income at Islamic Rural Banks, 2) Does CAR, NPF, FDR, NOM affect the BOPO, 3) Does CAR, NPF, FDR, NOM effect ROA, 4) Does operational cost per operating income affect profitability, 5) Does BOPO mediate CAR, NPF, FDR, NOM on profitability. The objectives of this study are: 1) To describe how CAR, NPF, FDR, NOM, Operational Costs on Operational Income in Islamic Rural Banks, 2) Test and analyze the effect of CAR, NPF, FDR, NOM on BOPO, 3) Test and analyze the effect of CAR, NPF, FDR, NOM on ROA, 4) Test and analyze the effect of operating costs per operating income on Profitability, 5) Test and analyze the effect of BOPO mediating CAR, NPF, FDR, NOM on Profitability.The results showed that the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing NPF, Net Operating Margin (NOM) had a significant positive effect on return on assets while operating costs per operating income had a negative effect on return on assets. return on assets. For further results, the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), has a significant positive effect on BOPO, while the Financing to Deposit Ratio (FDR), Net Operating Margin (NOM) has a negative significant impact on BOPO and BOPO mediates a significant negative impact on BOPO. Return on Assets.